ANTIMICROBIAL ACTIVITY OF EXTRACTS AND TOPICAL PRODUCTS OF THE STEM BARK OF SPATHODEA CAMPANULATA FOR WOUND HEALING - Ofori-Kwakye, K.; Kwapong, A. A.; Adu, F. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The antibacterial activity of the aqueous, ethanol, methanol and petroleum ether Soxhlet extracts of sundried stem bark of Spathodea campanulata P. Beauv. (Bignoniaceae) was investigated by testing the extracts against B. subtilis, E. coli, P. aeruginosa and S. aureus. The minimum inhibitory concentration (MIC) of the methanol extract was determined against the four bacteria strains and C. albicans using the broth dilution method. Four topical products were prepared by incorporating the methanol extract of S. campanulata (20 % w/w) into aqueous cream, soft paraffin, emulsifying ointment and simple ointment bases and evaluated for their in vitro antimicrobial efficacy. The effect of storage time on the activity of the methanol extract of S. campanulata and S. campanulata extract incorporated in aqueous cream base was also investigated. The methanol and ethanol extracts showed good activity while the aqueous and petroleum ether extracts exhibited little activity. The methanol extract showed the best antibacterial activity. The MIC of the methanol extract of S. campanulata was: C. albicans (45 - 50 mg/ml), B. subtilis and E. coli (50 - 55 mg/ml), P. aeruginosa (60 - 65 mg/ml), S. aureus (145 – 150 mg/ml). Antimicrobial activity of S. campanulata in the topical bases was in the order: aqueous cream > emulsifying ointment > simple ointment > white soft paraffin. Antimicrobial activity of S. campanulata in aqueous cream decreased (p < 0.05) upon storage at room temperature for 6-months. The antifungal activity of the methanol extract of S. campanulata was reduced (p < 0.05) upon storage while antibacterial activity was largely unaffected.